PENGARUH PENGGANTI LIMBAH PECAHAN GENTENG SOKKA DALAM PEMBUATAN BETON TERHADAP KUAT TEKAN BETON - Subaidillah Fansuri; Anita Intan Nura Diana; Dwi Deshariyanto (Fakultas Teknik, Universitas Wiraraja, 2020)
The research aims to see the effect of substitute tile waste waste in making concrete on concrete compressive strength. as a fine aggregate of the compressive strength of concrete as well as knowing the optimum compressive strength of concrete after the addition of powder waste from roof tiles as fine aggregate. Making concrete using sokka tile waste powder is expected to be able to utilize sokka tile waste powder that is no longer in use. The experimental method used in this research method. A normal concrete experiment was carried out with 20 MPa concrete quality which was given roof tile waste with variations of 0%, 10%, 20%, 30%, 40% and 50% of the weight of fine aggregate and compressive strength was tested with a sample specimen shaped cube size 15 x 15 x 15 cm at the age of 14 days. Effect of tile powder substitutes from mixed variations of 10%, 20%, 30%, 40%, 50%. This means that the variation of the tile roofing mixture mixture used has a simultaneous effect on the compressive strength of concrete. From the results of data analysis using the SPSS 20 for windows program which shows the value of tcount = 2.504> ttable = 1.745 so that it can be concluded that there is a significant effect between substitute variations in tile powder replacement on the value of concrete compressive strength. The use of tile powder more than 20% of the weight of the fine aggregate used has increased significantly, but not more than 50%. From this it can be concluded that the maximum compressive strength of concrete after the addition of tile waste is at the addition of 20% -50% tile waste with a concrete compressive strength value of 310-385 kN, which can be seen in the crushed pressure value in table 3 (concrete compressive strength test results).